Short run performance of initial public offerings : study on technology stocks listed on Nasdaq. - Ng, Chee Sum. (2008)
This article investigates the short run stock performance of technology firms after their initial public offering (IPO). A total of 50 companies are included in the model as we examine the impact of the following factors on their share performance: effectiveness of window of opportunity, age of the issuing company, gross proceeds from the issue and reputation of the lead underwriter handling the issue.